2020
DOI: 10.3390/metabo10020071
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Glutathione Redox Status in Clinical Samples by Two-Step Alkylation with N-ethylmaleimide Isotopologues

Abstract: Determination of the ratio of reduced to oxidized glutathione is of profound clinical interest in assessing the oxidative status of tissues and body fluids. However, this ratio is not yet a routine clinical parameter due to the analytically challenging interconversion of reduced (free) glutathione to oxidized (bound) glutathione. We aimed to facilitate this ratio determination in order to aid its incorporation as a routine clinical parameter. To this end, we developed a simple derivatization route that yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…The amount of GSH was higher (approximately seventeen times) than that of GSSG. Tomin and colleagues [ 50 ] suggest that serum values can be up to 6 times of those values found in the plasma due to the possible hemolysis that occurs during the coagulation process. In addition, the detection of other thiols in extracellular fluids (e.g., cysteine) may overestimate the concentration of GSH and oxidation artificial of GSH during sample deproteination with acids, which can lead to marked overestimation of GSSG [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of GSH was higher (approximately seventeen times) than that of GSSG. Tomin and colleagues [ 50 ] suggest that serum values can be up to 6 times of those values found in the plasma due to the possible hemolysis that occurs during the coagulation process. In addition, the detection of other thiols in extracellular fluids (e.g., cysteine) may overestimate the concentration of GSH and oxidation artificial of GSH during sample deproteination with acids, which can lead to marked overestimation of GSSG [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significantly increased body defense capacity against oxygen reactive species is also related to the GSH/GSSG ratio. GSH, the reduced form, should have a higher concentration than GSSG, the oxidized form [ 42 ]. In the present study, NSO treatment raised the GSH/GSSG ratio with almost half of its basal value.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an LC-MS/MS method using NEM derivatization has been developed and validated for the analysis of GSH and GSSG in porcine hepatocytes [ 16 ] and the assessment of the thiol redox metabolome in blood, urine, and saliva, employing a Waters Xevo TQ-S triple quadrupole mass spectrometer [ 17 ]. Tomin et al [ 18 ] also reported an LC-MS/MS-based protocol, employing an AB Sciex 4000 QTRAP ® mass spectrometer, for the measurement of GSH and GSSG in blood, tissue, and cultured cells in a single analysis. In that protocol, GSH was derivatized with NEM, the reagent was removed and GSSG was reduced to GSH by TCEP (Tris (2-carboxyethyl) phosphine) and then derivatized by d5-NEM ( N -ethyl-d5-maleimide) to generate GSH-d5-NEM.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report an optimized and simple method for the in-situ derivatization of GSH in cell culture that involves the incubation of cells in PBS-buffered NEM before methanolic extraction of GS-NEM, GSSG, and other metabolites of interest. In addition, we explored the coupling of liquid chromatographic separation to on-line UV absorbance and selected ion monitoring on a QTOF-MS instrument that may lack in contrast to a triple quadrupole mass spectrometer [ 16 , 17 , 18 ] the required linear range for the simultaneous quantification of GSH as GS-NEM and GSSG, but allows for a far more comprehensive analysis of the metabolome without having to set transitions for known metabolites of interest. Finally, we tested the applicability of the method by demonstrating the impact of genetic ablation of the monocarboxylate transporters MCT1 and MCT4 on the GSH/GSSG ratio of colon cancer cells under oxidative stress as well as the effect that NADPH consuming neomorphic mutations in the isocitrate dehydrogenases IDH1/2 have on the reduction of GSSG to GSH.…”
Section: Introductionmentioning
confidence: 99%